ANALISIS YURIDIS PERJANJIAN ANGKUTAN MULTIMODA ANTARA PT WIJAYA KARYA (PERSERO) TBK DENGAN PT SILKARGO INDONESIA DI PROYEK PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA UAP (PLTU) KETAPANG 2X10 MW - Sriyono; Indah Kusuma Wardhani (Fakultas Hukum Universitas Borobudur, 2022)
In the construction of the Ketapang PLTU with a capacity of 2x10 MW in West Kalimantan, multimodal transportation is needed to send steel structure materials from Jakarta to Ketapang. Therefore, PT Wijaya Karya (Persero) Tbk cooperates with PT Silkargo Indonesia as a carrier, which is stated in the form of a multimodal transportation contract. Based on this description, the authors are interested in examining the problems regarding the process of the occurrence of a multimodal transport contract and the suitability of the multimodal transport contract with the regulations. To discuss these problems, normative and empirical juridical research methods are used. The conclusion is the process of the occurrence of a multimodal transport contract goes through two stages, namely the pre-contractual stage which includes announcements and invitations, explanations, submission of bid documents, document evaluation, clarification and negotiation, determination and announcement of winners, and the contractual stage which includes determination of carriers and signing of contracts. The multimodal transport contract is in accordance with the prevailing regulations, namely Government Regulation Number 8 of 2011 concerning Multimodal Transportation, in particular Article 4, Article 12 paragraph (1), Article 13, Article 16, Article 17, Article 19, Article 21, Article 22, Article 23 paragraph (1), Article 24, Article 25 paragraph (2), Article 25 paragraph (3), and Article 26.